2018
DOI: 10.1542/hpeds.2018-0061
|View full text |Cite
|
Sign up to set email alerts
|

Adherence to AAP Healthy Newborn Discharge Criteria in a Tertiary Care Children’s Hospital

Abstract: A B S T R A C TOBJECTIVES: In 2015, the American Academy of Pediatrics (AAP) published an updated consensus statement containing 17 discharge recommendations for healthy term newborn infants. In this study, we identify whether the AAP criteria were met before discharge at a tertiary care academic children's hospital. METHODS:A stratified random sample of charts from newborns who were discharged between June 1, 2015, and May 31, 2016, was reviewed. Of the 531 charts reviewed, 433 were included in the study. A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…Thirteen policy documents reported discharge readiness criteria [ 24 , 33 , 34 , 37 – 46 ]. Seventeen research documents reported readiness criteria, and these included nine research studies [ 11 , 12 , 25 , 31 , 32 , 35 , 47 49 ], three review articles [ 36 , 50 , 51 ], two commentaries [ 52 , 53 ], a thesis [ 54 ], a medical news article [ 55 ] and an unpublished evaluation report [ 56 ]. Policy documents were from the United States ( n = 3), Canada ( n = 2), India ( n = 2), England ( n = 1) and five of the policy documents had a global focus.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Thirteen policy documents reported discharge readiness criteria [ 24 , 33 , 34 , 37 – 46 ]. Seventeen research documents reported readiness criteria, and these included nine research studies [ 11 , 12 , 25 , 31 , 32 , 35 , 47 49 ], three review articles [ 36 , 50 , 51 ], two commentaries [ 52 , 53 ], a thesis [ 54 ], a medical news article [ 55 ] and an unpublished evaluation report [ 56 ]. Policy documents were from the United States ( n = 3), Canada ( n = 2), India ( n = 2), England ( n = 1) and five of the policy documents had a global focus.…”
Section: Resultsmentioning
confidence: 99%
“…physical exam, danger signs, pain/discomfort) 10 [59%] [ 11 , 12 , 31 , 32 , 47 , 49 , 50 , 53 , 55 , 56 ] 7 [54%] [ 37 , 39 , 41 – 43 , 45 , 46 ] Infant health (e.g. physical exam, danger signs, breastfeeding, vnutrition/weight status) 10 [59%] [ 32 , 35 , 36 , 47 , 50 – 53 , 55 , 56 ] 10 [77%] [ 24 , 33 , 34 , 37 , 41 – 43 , 45 , 46 ] Low birth weight (e.g. stable breathing, full feeds, sustained weight gain) 1 [6%] [ 25 ] 1 [8%] [ 24 ] Tests (e.g.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the most commonly missed items were timely pediatrician follow-up appointment, social risk factor assessment, observation of breastfeeding, and car seat education. 15 The NBC model is uniquely suited to both provide timely outpatient follow-up and to address the most commonly missed items. Of particular note is NBC's commitment to assuring safe and supported breastfeeding-education of mother and family, observed feeding sessions, and ongoing lactation support are all discrete items on the discharge readiness checklist.…”
Section: Discussionmentioning
confidence: 99%